Pengaruh Edukasi Media Audio Visual Terhadap Tingkat Pengetahuan Ibu Hamil Tentang Faktor Risiko Kehamilan di Wilayah Kerja Puskesmas Jejangkit - Rohana -; Rita Kirana; Erni Yuliastuti; Vonny Khresna Dewi (JURNAL KEBIDANAN BESTARI, 2026)
Abstract Pregnancy risk factors remain a maternal health issue in the Jejangkit Community Health Center working area. Data from June 2025 shows that there were 41 pregnant women, 13 of whom (31%) had high-risk pregnancies. This condition indicates the need to increase pregnant women's knowledge about pregnancy risk factors as a preventive measure against complications. Audio-visual media is an effective educational method because it can convey information in an interesting and easy-to-understand manner through a combination of visual and audio elements. This study aims to determine the effect of education using audio-visual media on the level of knowledge of pregnant women about pregnancy risk factors in the Jejangkit Community Health Center working area. This study used a pre-experimental design with a one group pretest-posttest design. The sample consisted of 41 pregnant women taken using total sampling technique. Data analysis used the Paired Sample t-Test with a 95% confidence level (α = 0.05). The Paired Sample t-Test results showed a p-value = 0.000 (p < 0.05), which means there was a significant effect. The average knowledge of pregnant women increased from 7.61 before the intervention to 10.20 after the intervention. Based on the results obtained, education using audio-visual media has a significant effect on increasing the knowledge of pregnant women about pregnancy risk factors in the working area of the Jejangkit Community Health Center. Keyword: Audio-Visual Media, Knowledge, Pregnant Women